Essence and features of Grover’s method implementation on a classical computer for symmetric cryptanalysis - Gorbenko, Yu.I.; Kaptyol, Ye.Yu. (Radiotekhnika, 2018)
This paper is devoted to detailing, mastering for use, checking cryptanalytic properties and demonstrating the use of Grover’s method for cryptanalysis of symmetric cryptographic transformations. The essence of the method and its refinement are presented in order to implement Grover’s quantum algorithm on a classical computer.